Camino a Bali: cambio climático y cambio social global - Iranzo, Juan Manuel (Nómadas. Critical Journal of Social and Juridical Sciences, 2008)
In 2007 climate change ceased to be a controversial matter and became an unquestionable fact and the leading issue of the international agenda. Joint concerns, global warming and peak oil –forecasting future scarcity and higher energy prices–, were sistematically adressed through appeals to human technological ingenuity and fostering market mechanisms. Political, economic and media authories did not resort to collective movilization for creative cooperation in prevention, adaptation and mitigation of climate change, but professed unanimosuly a form of ‘technological messianism’. The background of this attitud was overtly the struggle between nuclear and renewable energies industries to becom the major sustitutive source to fossil fuels and concealedly a choice for technocratic forms of public agenda management instead of popular movilization which could lead to contest of basic tenets of the sistem, such as throwing doubts about the compatibility of unrestrained GNP and rents growth and the sustainability of Nature as in its present condition for future generations. Climate change can be alternatively defined as a moral issue, insofar its about the moral value of preserving nature from the harms of growth and not about contesting growth as a core principle or the distributive effects of its globalized market-state sistem of regulation.